Take Control of Shortcuts - Orchard, Rosemary (Take Control Books, 2020)
Improve your iPad and iPhone workflows with automation! Version 1.1, updated 09/30/2020 Automation is no longer just for advanced Mac and PC users! Apple's Shortcuts app lets anyone with an iPhone or iPad automate day-to-day tasks, from the simple to the complex. This book is a complete introduction to Shortcuts, which covers every aspect of building, installing, debugging, running, syncing, and sharing shortcuts. It also includes step-by-step recipes for creating numerous useful shortcuts yourself. Apple's Shortcuts app brings extensive automation capabilities to your iPhone or iPad, using a drag-and-drop, fill-in-the-blanks interface much like Automator on the Mac. It lets you perform sequences of tasks, including ones that span various apps, with just a tap or a voice command-or even automatically when certain conditions are met. Shortcuts can save you time and effort, help you accomplish previously complicated tasks, and let you customize your device to better meet your needs. And with iOS 14/iPadOS 14, Shortcuts has become even more powerful than before. But for all its utility, Shortcuts is not self-explanatory, so it can be challenging to figure out its quirks and create effective, time-saving automations. That's where Take Control of Shortcuts comes in. Written by automation expert Rosemary Orchard, this book opens the world of iOS/iPadOS automation to users at every level. With Rosemary's help, you'll learn how to: Navigate the Shortcuts app: Understand the user interface and terminology, then install and run your first shortcut. Run shortcuts: Discover many different ways to run a shortcut, from tapping an icon to using Home automations, Siri, and Apple Watch. Build shortcuts: Start with simple, one-step shortcuts and work your way up to complex shortcuts with input, output, variables, conditionals, loops, and more. Debugging advice is also included. Install and sync shortcuts: Download and install shortcuts others have written, sync your shortcuts across your devices, and share them with other people. Then, to both illustrate the main principles you've learned and give you practical tools to get you started, Rosemary walks you step by step through the creation of 15 sample shortcuts, which you can also download and install using links in the book. Examples include: Event templates A daily overview Converting and sharing images Adding a song to a playlist Logging expenses Turning on lights automatically when you get home The book als...